2011
DOI: 10.1039/c1cp21332f
|View full text |Cite
|
Sign up to set email alerts
|

Self-doping of molecular quantum-dot cellular automata: mixed valence zwitterions

Abstract: Molecular quantum-dot cellular automata (QCA) is a promising paradigm for realizing molecular electronics. In molecular QCA, binary information is encoded in the distribution of intramolecular charge, and Coulomb interactions between neighboring molecules combine to create long-range correlations in charge distribution that can be exploited for signal transfer and computation. Appropriate mixed-valence species are promising candidates for single-molecule device operation. A complication arises because many mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…We assume that in addition to the mobile electronic charge, there are fixed neutralizing charges of þe/2 on each of the two dots. In the actual molecule, this neutralizing charge is either a donor center 13 or a counterion. 14,15 The model reflects the reality that molecular QCA cells have a nonzero dipole moment, but no net charge.…”
Section: A Systemmentioning
confidence: 99%
“…We assume that in addition to the mobile electronic charge, there are fixed neutralizing charges of þe/2 on each of the two dots. In the actual molecule, this neutralizing charge is either a donor center 13 or a counterion. 14,15 The model reflects the reality that molecular QCA cells have a nonzero dipole moment, but no net charge.…”
Section: A Systemmentioning
confidence: 99%
“…[2,3] QCA relies on encoding binary information into quantum-dots or molecules by the location of an electron or hole ( Figure 1). [3,5] To overcome this limitation, we sought the preparation of an eutral mixed-valence compound where the counterion is incorporated as part of the ligand backbone.D espite substantial interests in electron transfer processes,v ery few neutral mixed-valence compounds have been fully studied. Proof-of-concept QCA experiments have been realized utilizing metallic nanometer-scale quantum-dots, [4] and our interest lies in extending this paradigm to the molecular realm.…”
mentioning
confidence: 99%
“…Long range charge distribution for signal transfer was exploited with intramolecular charge distribution in neighboring objects. This study was concluded also into the cellular automata (Lu and Lent, 2011).…”
Section: Introductionmentioning
confidence: 91%